Analysis of the Utilization of Arabic Language Reference Collections at the UIMSYA Library for PBA Students - Mahbub Nawawi; Nur Maya Badriatul Jamroh (Divisi Penelitian Yayasan Simfoni Ilmu Cendekia, 2026)
This research is motivated by the phenomenon of low interest in visiting and utilizing references by Arabic Language Education (PBA) students at the As-Syafa’ah IAIDA Blokagung Library, which is suspected to be due to the lack of up-to-date Arabic literature collections. This study aims to determine the condition of the facilities and measure the effectiveness of Arabic language references for students in the Arabic Language Education (PBA) program. The method used is descriptive quantitative with a population of 156 students and a sample of 40 respondents taken thru the Simple Random Sampling technique. Data were collected thru observation, documentation, and questionnaires, then analyzed using simple linear regression thru SPSS software. The research results indicate that the current condition of library facilities and infrastructure is still categorized as minimal and does not yet meet the National Standards for Higher Education Libraries, particularly in the ratio of reading room area to the total number of students. Nevertheless, the hypothesis test results (t-test) show a t_hitung value of (5.973) > t_tabel (2.024), which means that Arabic language references have a significant effectiveness for PBA students. The R^2 value of 0.484 indicates that the Arabic language reference variable contributes 48.4% to the fulfillment of students' literature needs, while the remaining percentage is influenced by other factors. The research concludes that although the collection is effective, an increase in volume and an update of the literature are necessary to optimize the service.